Educação ambiental: um estudo de experiências nas escolas municipais de Natal - Gonzaga, Magnus José Barros (2008)
This a research on pedagogical experiences about Environmental Education carried out in selected schools of the municipal education net of the city of Natal, Rio Grande do Norte State. This study occurs in a where social and environmental problems reach great dimensions and provoke discussions all over the planet. Inside this social context where education is taken as a form intervention in the world, several methodological and theoretical approaches emerge indicating Environmental Education tendencies as different ways to face challenges due to environmental crisis. The maim question pursued by the research is to inquiry how schools have developed their Environmental Education experiences. Pedagogical experiences on Environmental Education are analyzed in selected schools having as theoretical framework ideas for social change, by human action accordingly to Hanna Arendt‟s thought, and Marx‟s idea of praxis, (1989). The objective is to identify, to know and to map the pedagogical experiences on Environmental Education carried out in selected schools of the municipality teaching net having sociological cartography as a methodological strategy for analyzing empirical data. The results of the research pointed out existing reductionist and behaviorist-pedagogical perspectives as for as Environmental Education is concerned as well as environmental understanding, showing a predominance of the conservative Environmental Education tendency inside schools